Tailoring Service Delivery Innovation Architecture: A Service-Dominant Logic Theory Perspective for Micro Small and Medium Enterprises - Moris Adidi Yogia; Syafaruddin Z; Septian Wahyudi; Cifebrima Suyastri (Media Ekonomi dan Manajemen, 2024)
Although extensively discussed in previous studies, social media adoption has yet to consistently translate into improved business performance, revealing a significant research gap. In light of this, our study seeks to bridge this gap by investigating the relationship between social media adoption and performance in 261 micro-businesses within the food and beverage sector. We aim to explore the role of distinctive competencies in marketing as a mediating variable and examine the influence of service delivery innovation architecture from the perspective of service-dominant logic theory. We employ SEM-Amos as our analytical tool to test the formulated hypotheses to achieve this. The result show that this study significantly advances SDL theory by elucidating the pivotal role of social media adoption in understanding customer behavior and gaining valuable insights. In the context of SDL, this contributes to the understanding of how services are co-created between businesses and customers in a digitally connected environment. The outcomes of this research offer valuable insights for small businesses on leveraging social media adoption to enhance their distinctive competencies in marketing and service delivery innovation architecture.